PERSPEKTIF YURIDIS FILOSOFIS GRASI BAGI NARAPIDANA - SOGE, MARKUS MARSELINUS (Politeknik Pengayoman Indonesia, 2024)
The government issued a discourse on granting mass clemency due to the overcrowded conditions of the Penitentiary. The discourse raises pros and cons in the community. In handling prisoners in the Penitentiary, a policy strategy is implemented, namely coaching to improve their readiness to return to the community. This study aims to determine the philosophical juridical perspective of clemency for prisoners. This research uses normative legal research methods with secondary data sources in the form of primary legal materials, namely related laws and regulations, which are collected using literature studies. The results of the study show that clemency is a pardon in the form of changes, relief, reduction, or abolition of criminal execution, to convicts or prisoners granted by the President. Because clemency is a pardon for convicts, the only party interested in clemency is the convict himself, who is free to use or not use his right to apply for clemency, in addition to the convict, namely the legal counsel and his family. The reasons for clemency are the interests of the family of the convicted person, the convicted person has contributed to society, the convicted person suffers from an incurable disease, and the convicted person has behaved well while in prison. Similarly, clemency can be used as a way out for a convict who is in such a heartbreaking situation that it is impossible for him/her to survive in Penitentiary.